Droit de vivre et identités biopolitiques: Право на живеење и биополитички идентитети - Mihali, Ciprian; Hadzi-Lega, Joana (Identities: Journal for Politics, Gender and Culture, 2006)
Author(s): Ciprian Mihali | Чипријан Михали Title (French): Droit de vivre et identités biopolitiques Title (Macedonian): Право на живеење и биополитички идентитети Translated by (French to Macedonian): Joana Hadzi-Lega | Јоана Хаџи-Лега Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 5, No 1 (Winter 2006) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 89-112 Page Count: 23 Citation (French): Ciprian Mihali, “Droit de vivre et identités biopolitiques,” Identities: Journal for Politics, Gender and Culture, Vol. 5, No 1 (Winter 2006): 89-112. Citation (Macedonian): Чипријан Михали, „Право на живеење и биополитички идентитети“, превод од француски Јоана Хаџи-Лега, Идентитети: списание за политика, род и култура, т. 5, бр. 1 (зима 2006): 89-112.